In vivo antibacterial activity and biochemical effects of methanol extract of Annona muricata leaves against multidrug- resistant Salmonella Typhimurium in Wistar rats - Fondeh, Brenda Mazongue; Awah, Laupy Anne; Ndip, Rita Ayuk; Kibu, Odette Dzemo; Ngemenya, Moses Njutain (International Journal of Basic & Clinical Pharmacology, 2025)
Background: The increasing antibiotic resistance and paucity of new antibiotics has contributed greatly to the high morbidity and mortality of salmonellosis necessitating the search for alternative treatments. Annona muricata has shown promising activity against multidrug-resistant (MDR) Salmonella in vitro but in vivo studies are rare. This study evaluated the activity of A. muricata, against MDR Salmonella Typhimurium in vivo. Methods: The minimum inhibitory concentration (MIC) of a methanol crude extract of A. muricata was determined by micro-dilution assay against a characterized MDR clinical S. Typhimurium strain. Wistar rats infected with 3 x 108 CFUs/mL of the MDR strain were treated with 50-200 mg/kg body weight of extract for 10 days. Faecal load of S. Typhimurium colonies was determined by the direct plate count technique on days 1, 5 and 10. Animals were sacrificed and blood was collected for biochemical analyses. Data were analysed using GraphPad Prism Software. Results: The S. Typhimurium strain was multidrug-resistant and the extract recorded a MIC of 2 mg/ml The extract produced a significant (p<0.001) dose-dependent reduction in Salmonella colonies in faeces of treated rats with a 100% inhibition recorded at 200 mg/kg body weight on day 10. Liver and renal function tests did not indicate any abnormalities (p<0.05). Conclusions: This is the first report of in vivo activity of A. muricata leaves against multidrug-resistant Salmonella. The high activity and lack of adverse toxicity supports it use in traditional medicine and hence is a potential treatment for resistant Salmonella infections.